Effect of Annealing Temperature On Iron Doped Titanium Dioxide Thin Films Prepared By Spin Coating Technique - Mukhtar Effendi; Bilalodin B (Department of Physics, Sebelas Maret University, 2016)
Iron (Fe) doped titanium dioxide (TiO2) thin films have been successfully deposited by using spin coating technique. X-ray diffraction (XRD) and Scanning Electron Microscope (SEM) were employed to characterize the microstructure and crystallite morphology of the films. It was indicated that the rutile crystal orientation appears due to increasing annealing temperature of the thin films. Furthermore, increasing annealing temperature of the thin films yielded an increasing of porosity value which is related to the application on gas sensor films.